CtIP-mediated DNA resection is dispensable for IgH class switch recombination by alternative end-joining - Wang, Xiaobin S. (Proc Natl Acad Sci U S A, 2020)
To generate antibodies with different effector functions, B cells undergo Immunoglobulin Heavy Chain (IgH) class switch recombination (CSR). The ligation step of CSR is usually mediated by the classical nonhomologous end-joining (cNHEJ) pathway. In cNHEJ-deficient cells, a remarkable ∼25% of CSR can be achieved by the alternative end-joining (Alt-EJ) pathway that preferentially uses microhomology (MH) at the junctions. While A-EJ-mediated repair of endonuclease-generated breaks requires DNA end resection, we show that CtIP-mediated DNA end resection is dispensable for A-EJ-mediated CSR using cNHEJ-deficient B cells. High-throughput sequencing analyses revealed that loss of ATM/ATR phosphorylation of CtIP at T855 or ATM kinase inhibition suppresses resection without altering the MH pattern of the A-EJ-mediated switch junctions. Moreover, we found that ATM kinase promotes Alt-EJ-mediated CSR by suppressing interchromosomal translocations independent of end resection. Finally, temporal analyses reveal that MHs are enriched in early internal deletions even in cNHEJ-proficient B cells. Thus, we propose that repetitive IgH switch regions represent favored substrates for MH-mediated end-joining contributing to the robustness and resection independence of A-EJ-mediated CSR.